Getting started in six sigma - Thomsett, Michael C. (John Wiley & Sons, 2005)
Six Sigma is designed to achieve excellence in customer service and measure deviation from the ideal. It provides a process for placing value on the intangible nature of quality control. The underlying theories of Six Sigma are highly technical and complex. This book is a basic guide to those who are new to the concept, and though this is a complex subject, the concepts involved are not too complex for readers to grasp